Microstructure and macro-mechanical properties of residual soil subjected to repeated hygroscopic cycles - Xu, Xu-tang; Chen, Xiang-long; Cai, Ye-qing; Xu, Xiang (Frontiers in Earth Science, 2025)
Residual soil widely distributed in Fujian region has the characteristics of strong structure and easy softening in contact with water, which limits the possibility of its beneficial utilization. This study investigates the impact of humid and hot environment on the strength characteristics of residual soil, and how changes in soil microstructure are correlated with strength attenuation. Residual soil with particle size distribution from gravel to clay was subjected to repeated hygroscopic cycle tests. Subsequently, unsaturated triaxial consolidation drainage shear (CD) and nuclear magnetic resonance (NMR) tests were carried out on the samples undergoing 0–7 hygroscopic cycles, and the damage mechanism of the soil was analyzed from macroscopic to microscopic scales. Results showed that the soil shear characteristics were influenced by the number of hygroscopic cycles and had a correlation with stress level (confining pressure and target suction), the greater the cumulative irreversible deformation and the more pronounced shear dilation characteristics of the soil had after more hygroscopic cycles and higher stress levels. The shear strength index of unsaturated soil after repeated hygroscopic paths presented a decreasing trend, but the attenuation of internal friction angle and suction friction angle was limited, and the average values were 21.3° and 14.7°, respectively. The T2 spectral distribution curve of soil was a trimodal pattern, and the content of small holes consistently decreasing as the cycling process progressed, while the percentage of macropores increased significantly. In view of the continuous dissolution of soluble minerals and cementing materials and the repeated release of suction in the soil, the internal particles of the soil were gradually loosened. Accompanied by the continuous expansion and penetration of intergranular pores, connecting cracks were ultimately formed. The above fatigue damage to the soil pore structure led to the attenuation of its macro-mechanical properties. Throughout the test, the saturated shear strength of the soil continued to decrease due to the interaggregate connection was always broken, while the destruction of the intergranular connection in the aggregate was relatively slow, and the internal friction angle in the soil implied a slow decrease and even stabilized at a later stage. The research results could provide a useful reference for a deeper understanding of the environmental damage effects on the soil macroscopic mechanical properties.